Modelling and simulation of hysteresis control algorithm for use in single phase ac-to-ac matrix converter / Seri Iryani Mohd Noor - Mohd Noor, Seri Iryani (2003)
This thesis is illustrated by developing computer simulation models of ac-to-ac single phase matrix converter (SPMC) using sinusoidal pulse width modulation (SPWM) technique and another algorithm i.e hysteresis control technique. The SPMC act as a frequency changer and the load were used in this simulation are passive load i.e resistance and inductance. As an ac-to-ac converter is a system that delivers ac power with the different amplitude, frequency and phase when energized from an ac source. The simulation models use the Power System Block Set (PSB) within the MatLab/Simulink (MLS). PBS provides the ability to model and simulate electrical power system and drives within simulink environment. Then the result will be compared with SPICE (Simulation Program with Integrated Circuit Emphasis). The obtained using of switching technique in power electronic is to control the voltage output or output frequency or both.